2004
DOI: 10.1108/00070700410539770
|View full text |Cite
|
Sign up to set email alerts
|

Whitening and sweetening influences on filter coffee preference

Abstract: As a basis for development of new, and rationalisation of existing products, consumer preferences in commercial filter coffees were examined in a quantitative approach with multivariate mapping. Coffees were brewed from 12 ground bean blends and served to 150 consumers as drunk normally – black, whitened and/or sweetened. In a complete block design with two sessions of six coffees, employing randomisation to reduce order effects, hedonic data on a five‐point scale were collected then processed using Q‐mode pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…우리나라 커피시장은 2011년 약 2조 8,000억 원으로 이 중 40%(약 1조 2,800억 원)를 차지하는 인스턴트 커피는 간편성과 보편성 때문에 한국의 커피 시장을 주도하 며 양적, 질적으로 꾸준한 성장을 이루고 있다 (2). 일반적으 로 커피의 쓴맛, 신맛, 떫은맛을 완화하기 위해 커피에 커피 크리머 등의 부재료를 첨가하는데(3), 전 세계 대부분의 소 비자들은 인스턴트커피 음용 시 부재료로 설탕(시럽) 및 크 리머를 첨가하는 것으로 나타났다 (4). 국내 소비자들의 부재 료 첨가비율이 현저히 높은 것은 국내에서 인스턴트커피, 특히 커피믹스의 소비가 높은 것(5)과 관련이 있다.…”
Section: 서 론unclassified
“…우리나라 커피시장은 2011년 약 2조 8,000억 원으로 이 중 40%(약 1조 2,800억 원)를 차지하는 인스턴트 커피는 간편성과 보편성 때문에 한국의 커피 시장을 주도하 며 양적, 질적으로 꾸준한 성장을 이루고 있다 (2). 일반적으 로 커피의 쓴맛, 신맛, 떫은맛을 완화하기 위해 커피에 커피 크리머 등의 부재료를 첨가하는데(3), 전 세계 대부분의 소 비자들은 인스턴트커피 음용 시 부재료로 설탕(시럽) 및 크 리머를 첨가하는 것으로 나타났다 (4). 국내 소비자들의 부재 료 첨가비율이 현저히 높은 것은 국내에서 인스턴트커피, 특히 커피믹스의 소비가 높은 것(5)과 관련이 있다.…”
Section: 서 론unclassified
“…Narain et al 2004 [7], carried out a sensory study in which they evaluated assessor preference (n = 150) in various filter coffee blends and examined segmentation. The assessors evaluated twelve different filter coffee samples, over two sessions, as they normally would consume coffee (with/without milk and sugar) and ranked them on a five-point scale.…”
Section: Resultsmentioning
confidence: 99%
“…Narain et al 2004 [7], also used a trained panel (n = 13) to profile the 12 commercial filter coffees when presented black unsweetened, white unsweetened and white sweetened; however, their results were focused on how each of the in- each other for two commercial coffee samples using RDA. Lundgren et al 1978, [58] reported that the ability of assessors to assess the degree of liking of sucrose levels in coffee beverages is independent of behavioural responses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations